2015
DOI: 10.1080/01494929.2015.1031422
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Relationship Education on Parental Attitudes

Abstract: Economically strained couples experience a multitude of chronic stressors and are at greater risk for lower quality relationships with their children. Relationship education (RE) programs indicate positive results for economically strained couples who attend. However, most studies examine relationship satisfaction or communication patterns with few addressing the influence of RE on parental attitudes. Therefore, we examined changes in parental attitudes for couples (n ¼ 70) and compared differences in parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…These findings are similar to other RE studies that examined PREP WMR's effectiveness in reducing emotional distress (Bradford, Hawkins, & Acker, 2015;Carlson et al, in press), particularly studies with low-income and ethnic minority populations (Amato, 2014;Carlson, Fripp, et al, 2014;Daire et al, 2012). WMR's flexible and streamlined format and low cost made it especially useful, compared to "traditional counseling," in these disadvantaged populations (Barden et al, 2015;Hawkins & Ooms, 2012). Combined with this published data and existing research on the deleterious impact and bidirectional influence of stress and emotional distress on CV disease, the current research suggests that the WMR program may be a viable and effective intervention for individuals diagnosed or at risk for CV disease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are similar to other RE studies that examined PREP WMR's effectiveness in reducing emotional distress (Bradford, Hawkins, & Acker, 2015;Carlson et al, in press), particularly studies with low-income and ethnic minority populations (Amato, 2014;Carlson, Fripp, et al, 2014;Daire et al, 2012). WMR's flexible and streamlined format and low cost made it especially useful, compared to "traditional counseling," in these disadvantaged populations (Barden et al, 2015;Hawkins & Ooms, 2012). Combined with this published data and existing research on the deleterious impact and bidirectional influence of stress and emotional distress on CV disease, the current research suggests that the WMR program may be a viable and effective intervention for individuals diagnosed or at risk for CV disease.…”
Section: Discussionsupporting
confidence: 83%
“…WMR’s flexible and streamlined format and low cost made it especially useful, compared to “traditional counseling,” in these disadvantaged populations (Barden et al, 2015; Carlson Daire et al, 2014; Hawkins & Ooms, 2012). Combined with this published data and existing research on the deleterious impact and bidirectional influence of stress and emotional distress on CV disease, the current research suggests that the WMR program may be a viable and effective intervention for individuals diagnosed or at risk for CV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the abovementioned studies of individual-oriented relationship education used PREP's Within My Reach (Antle et al, 2013;Carlson et al, 2017Carlson et al, , 2018. Wadsworth et al (2011) used an adapted version of the PREP curriculum (FRAME), as did Barden et al (2015;the Becoming Parents Program). While these studies provide preliminary support for individual-oriented RE, to our knowledge, no randomized controlled trials have been published testing the effects of individualoriented relationship education with a control condition.…”
Section: Individual Oriented Relationship Educationmentioning
confidence: 99%
“…Previous researchers indicated that parents participating in relationship education demonstrated improvements in parent–child relationships and noted decreases of child mental health difficulties within low-income families (Kirkland et al, 2011; Sterrett-Hong et al, 2018). Additionally, couples-oriented relationship education demonstrated positive effects for increasing parental alliance (Carlson, Barden, et al, 2014) and parental attitudes (Barden et al, 2015). However, research examining parenting outcomes for relationship education is still relatively new (Cowan & Cowan, 2014), and many of the RE studies that examined parenting benefits were pre–post designs, primarily focused on programs with couples attending together.…”
Section: Family Relationships For Economically Vulnerable Parentsmentioning
confidence: 99%
“…Documentation and literature: The literature search identified 17 RCTs and two follow-up studies, as well as several pre-post studies. Only two pre-post studies were eligible for the purposes of this evaluation (Barden et al, 2015;Carlson et al, 2014).…”
Section: Authors: Piia Karjalainen and Marko Merikukkamentioning
confidence: 99%